The locus coeruleus influences behavior by coordinating effective integration of fear memories and sensory input. - Haoyu Duan; Tianyu Wang; Xinyang Zhang; Dan Xia; Zeyi Wang; Tsz Hei Fong; Tianxiang Li; Rongzhen Yan; Yang Zhan; Yulong Li; Wen-Jun Gao; Qiang Zhou (PLoS Biology)
An essential function of memory is to guide behavior for better survival and adaptation. While memory formation has been extensively studied, far less is understood about how memory retrieval influences behaviors. In the auditory Pavlovian threat conditioning paradigm using C57BL/6J mice, retrieving a conditioned threat memory is associated with spiking in two dorsomedial prefrontal cortex (dmPFC) neurons with transient (T-neurons) and sustained (S-neurons) patterns. We show here that T-neurons and S-neurons are two distinct neuronal populations with different neuronal and synaptic properties and mRNA profiles. S-neuron spiking matches freezing behavior and is required for freezing. This sustained activity in S-neurons requires auditory inputs and the release of norepinephrine (NE) in the dmPFC. The activation of the locus coeruleus (LC) is initiated by dmPFC T-neuron inputs, sustained by auditory inputs, and is required for the transition to freezing by enhancing S-neuron activity. Interestingly, LC activation precipitates a brief period during which nonconditioned cues also induce freezing. Our findings highlight the critical contribution of the LC/NE system in the transition from memory to behavior, which coordinates the effective integration of memory, sensory inputs and emotional state for optimal adaptation.